Plasma panel‐based radiation detectors. Issue 1 (6th May 2013) - Friedman, Peter; Ball, Robert; Beene, James; Benhammou, Yan; Ben‐Moshe, Meny; Bentefour, Hassan; Chapman, J. W.; Etzion, Erez; Ferretti, Claudio; Levin, Daniel; Silver, Yiftah; Varner, Robert; et al.
Abstract The plasma panel sensor (PPS) is a gaseous micropattern radiation detector under current development. It has many operational and fabrication principles common to plasma display panels. It comprises a dense matrix of small, gas plasma discharge cells within a hermetically sealed panel. As in plasma display panels, it uses nonreactive, intrinsically radiation‐hard materials such as glass substrates, refractory metal electrodes, and mostly inert gas mixtures. We are developing these devices primarily as thin, low‐mass detectors with gas gaps from a few hundred microns to a few millimeters. The PPS is a high gain, inherently digital device with the potential for fast response times, fine position resolution (<50‐µm RMS) and low cost. In this paper, we report on prototype PPS experimental results in detecting betas, protons, and cosmic muons, and we extrapolate on the PPS potential for applications including the detection of alphas, heavy ions at low‐to‐medium energy, thermal neutrons, and X‐rays.